Characterization of Surface Modification of 347 Stainless Steel upon Shot Peening. (12th December 2017) - Li, Kejian; Zheng, Qiang; Li, Chunhong; Shao, Bin; Guo, Donglin; Chen, Dengming; Sun, Jianchun; Dong, Jiling; Cao, Pengjun; Shin, Keesam
Abstract : Plastic deformations, such as those obtained by shot peening on specimen surface, are an efficient way to improve the mechanical behavior of metals. Generally, scanning electron microscopy (SEM) and electron backscattered diffraction (EBSD) are commonly used to observe the complex microstructural evolutions, such as grain refinement and phase transformation, induced by the surface treatment. In this work, the microstructure of 347 stainless steel, after ultrasonic shot peening (USP) treatments, was investigated. SEM, EBSD, transmission electron microscopy, and X-ray diffraction were used to observe the microstructural evolutions, such as grain refinement and phase transformation. Deformation depth after the USP treatment was about 200  μ m. Grain size on the treated surface layer was about 100 nm, with two phases: austenite and α ′-martensite. The percentages of the austenite and α ′-martensite phases were 54% and 46%, respectively, which constitute an exact expression of the degree of plastic deformation on austenitic stainless steel.